Qu-Zhuo-Tong-Bi Decoction Alleviates Gouty Arthritis by Regulating Butyrate-Producing Bacteria in Mice - Wen, Xianghui; Lou, Yu; Song, Siyue; He, Zhixing; Chen, Juan; Xie, Zhijun; Shi, Xiaowei; Wen, Chengping; Shao, Tiejuan (Frontiers in Pharmacology, 2021)
Qu-zhuo-tong-bi decoction (QZTBD) is a traditional Chinese medicine prescription used to treat hyperuricemia and gout with no obvious adverse effects. However, the mechanism by which QZTBD treats gout has not been fully explored. Here, we investigated the effects of QZTBD on gouty arthritis and its therapeutic mechanism from the perspective of the gut microbiome. Our results demonstrated that QZTBD was effective for reducing serum uric acid level and attenuating paw edema and mechanical allodynia. QZTBD promoted the abundance of butyrate-producing bacteria and the production of SCFAs. Further study revealed that QZTBD restored the intestinal barrier function, modulated the expression of GPR43 and ABCG2, suppressed the activity of key glycolysis-related enzymes, and inhibited the generation of intestinal inflammatory factors. These findings suggested that QZTBD is an effective therapeutic drug for gouty arthritis. Butyrate-producing bacteria and its metabolites SCFAs might act as a potential target of QZTBD.